REKAYASA JOB MIX BETON RINGAN MENGGUNAKAN HYDROTON DAN MASTER EASE 5010 - Agata Iwan Candra; Eko Siswanto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2018)
Concrete is a composite building material that functions very widely in the field of construction. This object is quite environmentally friendly in its application, because its existence can reduce the use of wood in the world of construction construction. But the size of the excess weight that is owned by the concrete structure when compared with wood is still less efficient, especially in the application for building construction with a building height of more than one floor. lighter.On this occasion we tried to use a number of aggregate combinations to design a lightweight concrete formula mix design to match the specified spec. The composition and aggregates that we use are type I portland cement, Master Ease 5010 additive, Hydroton, Batu Gombong as coarse aggregates and sand which are used as fine aggregates. Hydrotonini has hard and light characteristics. Shaped like spheres - small spheres measuring 1 - 2.5cm, usually used as alternative planting media in general. With such characteristics Hydroton is considered able to be used as a coarse aggregate substitute in the manufacture of lightweight concrete job mixes